CONSUMERS PREFERENCE TOWARDS WATERMELON IN SEMARANG - Nugroho Arifianto; Sri Wahyuningsih; Lutfi Aris Sasongko (Universitas Wahid Hasyim, 2008)
Consumer buy product and service to fulfill their needs. Need is natural, while pretension is unnatural need. The objective of this research is to find out the consumers preference towards watermelon in Semarang, the factors that influence the consumers in choosing watermelons in Semarang, the alternative fruit that replace watermelon, and kinds of watermelons mostly sold in Semarang. Research method used is descriptive method, the technique of location and respondents sampling use purposive sampling with the locations are on three main markets in Semarang and there are 90 respondents. Kind of data and data resources used are primary and secondary data by interviews and questionnaires as the data collection method. The primary and secondary data in this research are analyzed with tabulation and percentage analysis technique. This research has been conducted on July – August 2008. The result of this research shows that watermelon has not become the most preferred fruit for Semarang consumers, in choosing watermelon, the consumers have preferences in the taste and seedless. However, the alternative fruit chosen by the consumers is orange. And, preferred watermelon in Semarang is as follows: weight of 2 – 4 kg, red fleshed, and seedless. Keywords: consumer, preference, watermelon